2020
DOI: 10.3390/su12072992
|View full text |Cite
|
Sign up to set email alerts
|

Linking Changes in Land Cover and Land Use of the Lower Mekong Basin to Instream Nitrate and Total Suspended Solids Variations

Abstract: Population growth and economic development are driving changes in land use/land cover (LULC) of the transboundary Lower Mekong River Basin (LMB), posing a serious threat to the integrity of the river system. Using data collected on a monthly basis over 30 years (1985–2015) at 14 stations located along the Lower Mekong river, this study explores whether spatiotemporal relationships exist between LULC changes and instream concentrations of total suspended solids (TSS) and nitrate—as proxies of water quality. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 63 publications
2
24
0
Order By: Relevance
“…Beside the dam development in Mekong River Basin, climate change and land use change are also the crucial factors of sediment transport throughout the basin [69]. The instream sediment load and yield in the lower part of the Mekong River are likely influenced by the interaction between land use/land cover, rainfall-runoff, and anthropogenic activities within the basin [70]. Deforestation and agriculture expansion could change the landcover and alters basin erosion of the Mekong River [71].…”
Section: Spatio-temporal Sediment Load and Yield Of Mekong River Basinmentioning
confidence: 99%
“…Beside the dam development in Mekong River Basin, climate change and land use change are also the crucial factors of sediment transport throughout the basin [69]. The instream sediment load and yield in the lower part of the Mekong River are likely influenced by the interaction between land use/land cover, rainfall-runoff, and anthropogenic activities within the basin [70]. Deforestation and agriculture expansion could change the landcover and alters basin erosion of the Mekong River [71].…”
Section: Spatio-temporal Sediment Load and Yield Of Mekong River Basinmentioning
confidence: 99%
“…However, our results differ from other highly urbanized tropical regions in Brazil [23] where urbanization was the strongest driver of nutrient concentrations in rivers, and nonintensive subsistence-level agriculture did not increase water nutrient concentrations. Most fertilizer use occurs in Europe and the United States, although fertilizers are increasing in Asia [39], which is increasingly replacing subsistence cultivations with intensive agricultural activities [17]. Interestingly, we found that NO 3 − and TN were positively correlated to agriculture (crops) but were negatively correlated to rice paddies, showing that traditional rice cultivation was not associated with an increase of nitrogen concentration in our sites.…”
Section: Resultsmentioning
confidence: 56%
“…Most forested areas are in Laos and Cambodia, although high rates of deforestation have recently occurred [9]. Lowland areas are dominated by rice cultivation [17]. Most people live in urban areas, with lower population densities in agricultural areas.…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations